A multiphysics analysis of dish reflector antennas for radio astronomy applications - Ludick, D.; Venter, M.; Davidson, David; Venter, G. (2016)
© 2016 European Association of Antennas and Propagation. This work considers a combined structural-electromagnetic analysis of large dish reflector antennas typically used in radio astronomy. The effect of gravitational deformation on the radio telescope is quantified by a structural analysis conducted with a finite element solver. The deformed geometry is then analysed using a computational electromagnetic package from which the performance degradation can be assessed. This offers key insights into the operation of the radio telescope under the influence of external forces, such as gravity.